Զ. Խալափյանի ստեղծագործություևևերի բառապաշարի շերտերը և նրանց ոճական արժեքը - Անուշ Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
Khalapyan is from those writers who possess a unique ability to uses killfully different lexical layers of the national language.
Keywords: Philology; Linguistics; Language and Literature